Unit Cost Of Inpatient And Outpatient Services In The JKN Era - Aslina; Hermiaty Nasruddin; Iin Widya Ningsi (The International Journal of Medical Science and Health Research, 2025)
Background: Since the implementation of the National Health Insurance (JKN) in 2014, Indonesia's healthcare financing system has undergone significant changes, introducing a capitation scheme for primary care and INA-CBG's for referral care. This study reviews literature from 2020 to 2025 concerning the calculation of unit costs for inpatient and outpatient services within the JKN framework. The primary focus is on the alignment between tariffs and the factors influencing cost variations among healthcare facilities. Methods: A narrative literature review was conducted by searching electronic databases using relevant keywords. Qualitative analysis synthesized comparisons between unit costs and JKN tariffs, as well as the determinants of cost variability. The THUMB approach (Time, Human Resources, Material, Budget) is also discussed as a costing method. Results: Inpatient unit costs generally tend to be higher than INA-CBG's tariffs, resulting in a cost gap that requires careful management. Activity-Based Costing (ABC) provides more accurate cost estimations compared to the less precise THUMB method. Demographic factors, operational efficiency, and clinical management contribute to differences in costs across facilities. Optimizing the role of case managers and conducting periodic tariff evaluations are recommended to ensure the sustainability of the system. Conclusion: Effective unit cost management and the application of appropriate costing methods are crucial for achieving efficiency, equity, and quality of care within the JKN era.